Deje que $ f : X \rightarrow Y$ y $g : Y \rightarrow Z$ sean funciones invertibles. Demuestre que $g \circ f : X \rightarrow Z$ es invertible y que $(g \circ f ) ^{-1} = f^{-1} \circ g^{-1} $
¿Sería esto suficiente como una prueba?
$$ \begin{align} (g \circ f) \circ (f^{-1} \circ g^{-1}) &= g \circ ((f \circ f^{-1}) \circ g^{-1})\\ &= g \circ (I_Y \circ g^{-1})\\ &= g \circ g^{-1}\\ &= I_X\\ (f^{-1} \circ g^{-1}) \circ (g \circ f) &= (f^{-1} \circ (g^{-1} \circ g)) \circ f\\ &= (f^{-1} \circ I_Y) \circ f\\ &= f^{-1} \circ f\\ &= I_Z \end {align} $$